2013
DOI: 10.3233/jad-130617
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Alzheimer-Like Pathological Human Tau Induces a Behavioral Motor and Olfactory Learning Deficit in Drosophila melanogaster

Abstract: A key characteristic of Alzheimer's disease and other tauopathies is the progressive accumulation of neurofibrillary tangles mainly composed of hyperphosphorylated tau protein. In the present study, we use transgenic Drosophila melanogaster as a model to analyze in vivo the effect of expressing pseudophosphorylated tau (S199E/T212E/T231E/S262E tau) on pathological human tau (PH-tau) and on the FTDP-17 mutant R406W (PH-tauR406W). We used two different inducers that produced different levels of tau expression. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 72 publications
1
32
0
Order By: Relevance
“…We have shown that phosphorylation of tau is suffi cient to promote tau self-assembly into fi laments [29] and that phosphorylation at Ser 199 and 262 and Thr 212 and 231 is sufficient to convert tau into an D-like protein in cells [101] and in vivo in transgenic Drosophila [126] . On the basis of our results and the evidence reviewed here, we propose that the hyperphosphorylation of tau leads to neurodegeneration through microtubule disruption and the consequent decreases in neurotransmission a n d a x o p l a s m i c t r a n s p o r t ( F i g .…”
Section: Discussionmentioning
confidence: 95%
“…We have shown that phosphorylation of tau is suffi cient to promote tau self-assembly into fi laments [29] and that phosphorylation at Ser 199 and 262 and Thr 212 and 231 is sufficient to convert tau into an D-like protein in cells [101] and in vivo in transgenic Drosophila [126] . On the basis of our results and the evidence reviewed here, we propose that the hyperphosphorylation of tau leads to neurodegeneration through microtubule disruption and the consequent decreases in neurotransmission a n d a x o p l a s m i c t r a n s p o r t ( F i g .…”
Section: Discussionmentioning
confidence: 95%
“…Several disease-linked mutations in the Tau gene affect correct splicing of its MT binding sites, thus enhancing abnormal phosphorylation and detachment of the protein. Both steps are believed to be crucial in the process of forming paired helical filaments and higher order neurofibrillary tangles [65,66]. …”
Section: Introductionmentioning
confidence: 99%
“…This neuronal loss and synaptic degeneration are caused by the presence of plaques and tangles [85]. Consistently, several studies showed that Drosophila AD models are also impaired in learning and memory [11, 8688], which makes Drosophila a useful model of the defective brain functions of AD.…”
Section: Drosophila As a Model System For Neurodegenerative Diseasesmentioning
confidence: 88%